Cloudberry (Rubus chamaemorus) and its components as chemopreventive constituents in ApcMin mice and human colon adenocarcinoma cells - Päivärinta, Essi (Helsingin yliopisto, 2017)
A diet rich in fruits and vegetables has been suggested to decrease the risk of colorectal cancer and the protective effects of these foods could probably be at least partly mediated by their polyphenolic compounds. The number of different polyphenols is huge and their effects on cells and tissues may differ. The promising results on chemopreventive effects of ellagitannin-rich pomegranate suggest that the other dietary sources of ellagitannins may also be effective in cancer prevention. The overall aim of the research reported in this thesis was to study the effects of cloudberry (Rubus chamaemorus), which is rich in ellagitannins, on all phases of intestinal tumour development. Specifically, the effects of cloudberry on the first two phases of carcinogenesis, initiation and promotion, were studied using the ApcMin mouse model. In addition, the effects of cloudberry extract on the indicators of the last phase of cancer development, progression and metastasis, and particularly cancer cell migration that is essential for this phase, were studied using scattering and wound healing assays in hepatocyte growth factor-induced HT29 and HCA7 human colon adenocarcinoma cell lines. A whole-cloudberry diet containing 10% (w/w) freeze-dried cloudberries significantly decreased the number and size of intestinal adenomas in ApcMin mice. In contrast, cloudberry seeds, cloudberry pulp, or pure ellagic acid, when incorporated into the diets in concentrations that corresponded to the whole-cloudberry diet, had no apparent effect. The effects of cloudberry on the development of adenomas were also compared with the effects of bilberry (Vaccinium myrtillus), which is rich in anthocyanins. Both berries decreased the number of adenomas, but their effects of adenoma size were different: thus, the adenoma size was decreased by cloudberry and increased by bilberry in comparison to the control diet. The opposite effects of the berries on tumour growth were associated with the changes in the gut microbiota, intestinal immunity, and the ...